SUCCESSFUL TREATMENT OF ENDOCARDITIS WITH PRESENTATION IN A KIDNEY TRANSPLANT PATIENT - CASE REPORT - Usprcov, Julijana; Karanfilovik, Angela Kabova; Karanfilovski, Vlatko; Spasovska, Adrijana; Tanevska, Aleksandra Canevska; Shterjova, Zaklina; Severova, Galina; Arnaudova, Frosina; Jovkovski, Aleksandar; Bushljetikj, Oliver; Gerakaroska, Marija; Jovev, Sasho; et al. (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Infective endocarditis (IE) is a serious complication in patients with transplanted kidney, leading to graft loss and a high mortality rate. We present a case of native valve endocarditis in a 51-year-old male with transplanted kidney that had atypical clinical course. The patient experienced prolonged subfebrile temperature with paroxysmal arrhythmia and development of cardio-pulmonary insufficiency. Transthoracic echocardiography (TTE) set the diagnosis of aortic valve vegetation with severe aortic regurgitation and pulmonary edema. We failed to isolate a microbiological agent, but all blood cultures were taken under antibiotic therapy. The patient was treated with surgical replacement of the native aortic valve with mechanical heart valve with significant clinical improvement. Ten days after the intervention, he was discharged with reduced markers of inflammation and proper function of the kidney graft. Immunosuppressive therapy was gradually reinstated. One year later, the patient was clinically stable and with proper graft function. Early diagnostic and therapeutic intervention, particularly intensive antibiotic therapy and surgical management can preserve the patient and the kidney allograft. Key words: kidney transplantation, endocarditis,cardiac surgery.